Effect of inherited aerobic capacity on neural plasticity in hippocampus - Laitinen, Paavo (2019)
Neural plasticity in hippocampus is a prerequisite for cognitive functions such as memory and learning. Different forms of neural plasticity include changes in the working of synapse functions, production of new neurons i. e. neurogenesis, and changes in microglia, that are cells of the immune system. Aging and neurodegenerative diseases result in cognitive decline and can impair hippocampal functions. Aerobic exercise has shown to improve cognitive functions and to increase plasticity markers in hippocampus. However, the role of intrinsic aerobic capacity is not as well known. The purpose of this thesis was to study the effect of intrinsic aerobic capacity and age on different forms of neural plasticity: synaptic plasticity and neuronal activation, neurogenesis and microglia activation. The study used an animal model with heterogenic rats that were selectively bred to have high aerobic capacity (HCR) or low aerobic capacity (LCR). The animals were kept sedentary and divided to four groups: young HCR (n = 9), young LCR (n = 10), old HCR (n = 12) and old LCR (n = 10). The young animals were euthanized at ~8 weeks and old animals at ~40 weeks of age. Four different regions of the hippocampus were analyzed: CA1, CA3, dentate gyrus (DG) and granule cell layer (GCL). Antibodies for microglia, neuronal activation, and neurogenesis were used for immunohistological analysis of hippocampus. Western blotting was used to determine expression of synaptic plasticity proteins and microglia in hippocampal homogenate. The present results demonstrate that expression of synaptic plasticity proteins SYN-1 and SYP was higher in younger animals, but the results were inconsistent between the HCR and LCR lines, and there were no differences in neuronal activation between groups. The number of newborn neurons was significantly higher in younger compared to older rats, and in the HCR compared to LCR animals. The number of Iba-1 positive cells was higher in older animals. Density of activated microglia was significantly higher in the inner part of GCL of DG compared to other analyzed hippocampal regions. Moreover, activated microglia in that region were negatively associated with the number of newborn cells in hippocampus, which are located roughly in the same region. Rats with high aerobic capacity showed increased neurogenesis compared to those with low aerobic capacity. This may be accompanied by increased synaptic plasticity, but those results are inconclusive. Older animals tended to have higher numbers of activated microglia, and the negative correlation between microglia of inner parts of GCL in DG and newborn cells suggests that activated microglia may downregulate neurogenesis. Thus, better intrinsic aerobic capacity seems to promote hippocampal neurogenesis, while aging and activation of microglia seem to be associated with impaired hippocampal neural plasticity.